The Impact of Pneumococcal Conjugate Vaccines on Pneumonia in Children: A Review of Recent Studies - Agustina, Putri Noviana; Agastya, Wayan Dhea (Journal of Diverse Medical Research: Medicosphere, 2024)
Background. The introduction of pneumococcal conjugate vaccines (PCVs) has significantly reduced the burden of pneumonia in children worldwide, leading to decreased hospitalization rates, lower severity of disease, and a reduction in antibiotic resistance. However, regional disparities persist, particularly in low- and middle-income countries where healthcare infrastructure and access to vaccines are often limited. Methods. This review synthesizes findings from recent studies on the impact of PCVs on the incidence, severity, and management of pneumonia in children. It includes analyses of studies conducted in various regions, highlighting the global and regional effects of PCVs on pneumonia hospitalization rates, vaccine effectiveness against severe disease, and antibiotic resistance. Discussion. The review underscores the importance of PCVs in reducing pneumonia-related hospitalization rates, disease severity, and antibiotic resistance globally. Nevertheless, challenges persist in addressing regional disparities, particularly in underserved areas with limited healthcare infrastructure and vaccine accessibility. Conclusion. Continued surveillance and research are essential to evaluate the long-term effectiveness of newer PCV formulations. Developing strategies to improve vaccination coverage in underserved populations and monitoring the emergence of new serotypes are critical for adapting public health strategies. By addressing these challenges, the protective benefits of PCVs can be sustained, ultimately improving health outcomes for children Keywords:Pneumococcal conjugate vaccine, pneumonia, children, hospitalization, vaccine effectiveness, antibiotic resistance